A Systematic Review of the Needs Assessment for Individuals with Physically and Intellectual Disabilities in Saudi Arabia: Challenges, Services, and Gaps - Zaino, Mohammad (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Background: Individuals with disabilities frequently face challenges in accessing healthcare services. Despite growing attention to disability inclusion worldwide, there remains a significant lack of comprehensive needs assessments for individuals with physical and intellectual disabilities in Saudi Arabia. Moreover, there is limited research integrating both quantitative and qualitative findings to provide an evidence-based roadmap for policy and intervention improvements. Objective: to systematically review the needs assessment for physically and intellectually disabled individuals in Saudi Arabia, focusing on the challenges they face, the services available to them, and the existing gaps in support. Methods: This study employed a qualitative approach to explore the barriers faced by individuals with physical and intellectual disabilities in Saudi Arabia. Semi-structured interviews were conducted with educators and caregivers who met specific selection criteria, including relevant experience in special education or caregiving roles. The interviews included open-ended questions to gather in-depth perspectives on educational, societal, familial, curricular, and behavioral challenges. Data collected from these interviews were transcribed and analyzed using thematic analysis with NVivo software. The analysis process involved coding the data, categorizing emerging themes, and ensuring credibility through strategies such as member checks and expert validation. Results: The study identified several critical barriers experienced by disabled individuals in Saudi Arabia. Educational challenges included a lack of specialized teacher training and inadequacies in addressing diverse learning needs. Societal obstacles, such as stigma and rejection, hindered social inclusion and acceptance. Familial constraints were noted, with limited parental engagement often caused by time pressures and a lack of knowledge. Curricular shortcomings highlighted the rigidity and inflexibility of current educational programs, which failed to cater to individual needs. Lastly, behavioral and emotional challenges, including self-injurious behavior and communication difficulties, were prevalent among disabled individuals. These findings underscore the urgent need for systemic reforms and collaborative efforts to improve support systems. Conclusion: This systematic review underscores the significant barriers faced by physically and intellectually disabled individuals in Saudi Arabia, ranging from limited accessibility in healthcare and public spaces to systemic challenges in education and parental involvement. It underscores the prevalence of physical disabilities (67.3%) among the studied population and identifies that 56.7% of individuals face notable barriers, such as inadequate infrastructure and insufficient specialized healthcare services. Quality-of-life assessments reveal a need for interventions to enhance physical and social inclusion.